2017
DOI: 10.47678/cjhe.v47i1.186485
|View full text |Cite
|
Sign up to set email alerts
|

Graduand Student Attributes: A Canadian Case

Abstract: The purpose of this qualitative case study was to gain insights into how academics understand undergraduate graduand attributes. The findings reveal some alignment in views about student attributes, including that they are engaged citizens, are self-directed, have imagination, are questioning, are flexible, display leadership, are problem solvers, and possess character. This consistency, however, does not include the spectrum of views on how these attributes are conceived and developed. The findings reveal a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Furthermore, the interactive and iterative process with the GAAP between instructors and their students created an engaging space where these two stakeholders can learn from each other. Kanuka and Cowly (2017) found that instructors share disengagement and mistrust regarding the implementation of GAs. By providing a confidential space for the instructors in the GAAP, they were able to assess and reflect on their own courses as they target and relate to GAs and the university experience as a whole.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the interactive and iterative process with the GAAP between instructors and their students created an engaging space where these two stakeholders can learn from each other. Kanuka and Cowly (2017) found that instructors share disengagement and mistrust regarding the implementation of GAs. By providing a confidential space for the instructors in the GAAP, they were able to assess and reflect on their own courses as they target and relate to GAs and the university experience as a whole.…”
Section: Discussionmentioning
confidence: 99%
“…They have control of their own profile and could generate course report. Students, on the other hand, have always been supportive of the GAs implementation and assessment (Kanuka and Cowley, 2017) as these transversal attributes can easily be mapped to employability attributes later, after their graduation.…”
Section: Discussionmentioning
confidence: 99%
“…The recommended implementation path and assessment of the student attributes was to be accomplished by program planners and instructors. An obstacle to implementation is the perception of whether or not these attributes are linked to program objectives, are developed and/ or addressed in the curriculum, would be linked to the curriculum, and could hence be assessed by instructors (Kanuka & Cowley, 2017). The implementation of UGAs as a set of outcomes acquired by students in higher education is a complex, multifaceted project.…”
Section: Introductionmentioning
confidence: 99%
“…Implementation has been slow in professional programs as accreditation-related graduate attribute assessment is already in place and the correspondence of the sets of professional and university graduate attributes is not obvious. In addition, the actual assessment of the UGAs is viewed as an obstacle by academics (Ipperciel & ElAtia, 2014;Kanuka & Cowley, 2017;Maguire & Gibbs, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation